Predictors of Change in Intrinsic Motivation Factors on Adolescent Science Learning - Moonika Teppo; Regina Soobard; Miia Rannikmäe (Science Education International)
Non-cognitive factors, such as motivation, have shown to play a significant role in adolescences science learning. However, there is little longitudinal research investigating students’ intrinsic motivation in science learning over school years. Based on self-determination theory, this study examines the change in, and associations between, students’ intrinsic motivation factors, such as interest/enjoyment, perceived competence, and perceived choice toward science learning over a 3-year period. Utilizing data from 171 lower secondaryschool students who have twice completed a self-reported questionnaire - first in grade 6 and 3 years later in grade 9, the predictive associations of perceived competence and perceived choice on interest/enjoyment are examined across time using structural equation modeling. The resultsindicate thatstudents’interest/enjoyment and perceived competence toward science learning significantly decrease over time, whereas the perceived level of choice remains the same. The results show that perceived choice significantly positively predicted the variance of interest/enjoyment and perceived competence, both in grades 6 and 9. However, perceived competence not directly predicted adolescents’ interest/enjoyment in science learning. Based on the results, it is argued that there is a need to enhance students’ perceptions of choice and competence for promoting interest and motivation in science learning at school.